(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study concentrates on the economic analysis of determinant factors of spiritual tourist expenditure in Tirunelveli District. In this study an effort has been taken to examine the dimensions of spiritual tourism in Tirunelveli District. This study covers the important spiritual tourist place of Tirunelveli district. It is confined to study the determinant factors of spiritual tourist expenditure, factors influencing their tour decisions and patterns of their visits. In spiritual tourism a tourist seeks peace of mind and a sense of spiritual satisfaction. Even though the visitors to the spiritual tourist spots of Tirunelveli are satisfied with peaceful atmosphere, they experience the unfriendliness of the local people, they are dissatisfied with the basic infrastructures like sanitation and drinking water facilities, lack of cleanliness and exploitation by the local vehicle operators. It these problems are addressed properly and enough publicity is given the spiritual tourism avenues of the Tiruchendur shall be explored to the optimum level. The study reveals that the regression analysis shows that the educational qualification, monthly income, stays in days and size of family are determined the total tour expenditure.